Exercise-Induced Hypertension Is Associated With Gestational Hypertension Occurrence in Patients With Repaired Aortic Coarctation - Carrie A. Zografos, MD; Elena Wadden, MD; Catherine M. Albright, MD; Jill M. Steiner, MD; Jonathan Buber, MD (JACC: Advances)
Background: Patients with repaired aortic coarctation (rCoA) are at risk of having exercise-induced hypertension (EIH) even with normal resting blood pressure (BP). A similar hypertensive response may occur during pregnancy, yet whether EIH is predictive of future gestational hypertension (GHTN) occurrence in rCoA patients is unknown. Objectives: The aim of this study was to evaluate for an association between EIH and subsequent occurrence of GHTN in patients with rCoA with normal resting BP. Methods: Patients seen at a cardio-obstetrics clinic at a quaternary center between January 2011 and April 2023 were included. All participants underwent echocardiogram and cardiopulmonary exercise testing in the year before pregnancy, BP was measured every trimester, and an echocardiogram was performed during pregnancy. Associations between exercise and pregnancy BP were evaluated using Pearson correlation, and predictors of GHTN were assessed using logistic regression. Results: Of 88 patients screened, 32 met inclusion criteria (average age, 29 ± 4 years, none had significant recurrent coarctation or more-than-mild aortic valve disease). During pregnancy, GHTN occurred in 10 patients (31%), 3 of whom had pre-eclampsia. Prior miscarriages, prior hypertensive disorders of pregnancy, and EIH were associated with occurrence of GHTN/pre-eclampsia, whereas body mass index and lack of aspirin use were not. In a multivariable analysis, EIH was independently associated with a 3-fold increase in the risk of developing GHTN. Patients with GHTN more frequently had abnormal global longitudinal strain on echocardiogram and lower peak oxygen consumption on cardiopulmonary exercise testing. Conclusions: EIH may be an important predictor for the occurrence of GHTN in patients with rCoA.